The impacts of TRIPS on the pharmaceutical regulation and pricing of drugs in Bangladesh: In search of policy direction. Issue 3 (8th May 2017) - Azam, M. Monirul
Abstract : Purpose: This paper aims to analyse the impacts of the Agreement on Trade Related Aspects of Intellectual Property Rights (TRIPS Agreement) as adopted by the World Trade Organization (WTO) on the pharmaceutical regulation and pricing of drugs in Bangladesh. The purpose of this paper is to explore how Bangladesh could adjust obligations for patent and pharmaceutical law reforms in the context of TRIPS Agreement while maintaining societal goals to ensure access to medicines. Another prime objective of this study is to examine viability of arguments regarding pharmaceutical patents for affordability and accessibility of pharmaceuticals in Bangladesh. Design/methodology/approach: This paper used doctrinal research and case study using surveys and interviews in Bangladesh to understand the perceptions of different stakeholders regarding TRIPS and possible impacts on the local pharmaceutical industry and also consequences as to access to pharmaceuticals in terms of pricing, availability and affordability. Findings: This study suggests that in the case of Bangladesh, the main health bottleneck is not patents or any drugs, but the lack of proper healthcare service, health infrastructure and lack of efficient healthcare personnel. Again, most of the necessary drugs for the local market are off patent, but patented drugs, issues of price, availability and affordability could become a concern for Bangladesh in situation of multi-drug resistance and for diseases like HIV AIDS, cancer and cardio-vascular problems. Research limitations/implications: This study was based on randomly selected interview and surveys. To get a broader picture of the impacts of TRIPS compliant patent law and pharmaceutical patents in a country like Bangladesh, more in-depth socio-legal studies need to be conducted. Due to shortage of time and resources, it was not possible to conduct broader socio-legal studies; therefore, this study may not reflect views of all related stakeholders. Practical/implications: This paper will guide how countries like Bangladesh could adopt intellectual property policies for pharmaceuticals in a way not only adjusting societal goals for accessibility and affordability of pharmaceuticals but also promoting innovation and capability of local industries. Social/implications: Countries like Bangladesh should adopt intellectual property policies balancing not only investment and innovation side but also societal goals to ensure access to medicines for the vast majority of poor populations. Originality/value: This study is an original study based on primary sources as collected during field studies in Bangladesh. It also used doctrinal research, and related materials are duly referred.